Monetary Aspects of Business Cycles in Norway. An Exploratory Study Based on Historical Data - Leo Andreas Grünfeld (Statistics Norway, Research Department, 1994)
Based on the methodology developed by Hodrick & Prescott (1980), it is shown that monetary activity in Norway by no means obeys the cyclical patterns described by Lucas (1983). By constructing annual time series covering monetary data from 1900 to 1992, combined with the use of varying filtering parameter values, it is demonstrated that only credit volume has followed a procyclical pattern. Furthermore, prices are found to be countercyclical during the post war period. Tests of relative volatility and cyclical skewness are presented as well as prospects for future studies of business cycles in Norway based on historical data.
Keywords: N13; N14; E32; 330; Business cycles; history of monetary activity.